Evidence for short-term, but not long-term, transfer effects in the temporal preparation of auditory stimuli. Issue 11 (November 2019) - Crowe, Emily M; Kent, Christopher
Starting procedures in racing sports consist of a warning (e.g., "Set") followed by a target (e.g., "Go") signal. During this interval (the foreperiod), athletes engage in temporal preparation whereby they prepare to respond to the target as quickly as possible. Despite a long history, the cognitive mechanisms underlying this process are debated. Recently, it has been suggested that traces of previous temporal durations drive temporal preparation performance rather than the traditional explanation that performance is related to the currently perceived hazard function. Los and colleagues used visual stimuli for the warning and target signals. As racing sports typically rely upon auditory stimuli, we investigated the role of memory on temporal preparation in the auditory domain. Experiment 1 investigated long-term transfer effects. In an acquisition phase, two groups of participants were exposed to different foreperiod distributions. One week later, during a transfer phase, both groups received the same distribution of foreperiods. There was no evidence for transfer effects. Therefore, Experiment 2 examined short-term transfer effects in which acquisition and transfer phases were completed in the same testing session. There was some evidence for transfer effects, but this was limited, suggesting that there may be modality-specific memory differences.